2002
DOI: 10.1038/416301a
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in one-dimensional monatomic metal chains

Abstract: Two-dimensional systems, such as ultrathin epitaxial films and superlattices, display magnetic properties distinct from bulk materials. A challenging aim of current research in magnetism is to explore structures of still lower dimensionality. As the dimensionality of a physical system is reduced, magnetic ordering tends to decrease as fluctuations become relatively more important. Spin lattice models predict that an infinite one-dimensional linear chain with short-range magnetic interactions spontaneously brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

38
803
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 843 publications
(860 citation statements)
references
References 26 publications
38
803
1
6
Order By: Relevance
“…However, our calculated results show that the magnetic anisotropy energy in both [V(Bz)] ∞ and [Mn(Bz)] ∞ polymers is smaller than 0.1 meV/TM, indicating that the ferromagnetism in these polymers might be stabilized only at extremely low temperature by the magnetic anisotropy induced barrier. There are also some reports, indicating the existence of FM in 1D chains with finite length, where the length of the chains is related to the range of the exchange interaction [25]. The most relevant work related to the current study is the discovery of FM in 1D V n (Bz) n+1 sandwich clusters by Miyajima et al [7] as mentioned above.…”
mentioning
confidence: 56%
“…However, our calculated results show that the magnetic anisotropy energy in both [V(Bz)] ∞ and [Mn(Bz)] ∞ polymers is smaller than 0.1 meV/TM, indicating that the ferromagnetism in these polymers might be stabilized only at extremely low temperature by the magnetic anisotropy induced barrier. There are also some reports, indicating the existence of FM in 1D chains with finite length, where the length of the chains is related to the range of the exchange interaction [25]. The most relevant work related to the current study is the discovery of FM in 1D V n (Bz) n+1 sandwich clusters by Miyajima et al [7] as mentioned above.…”
mentioning
confidence: 56%
“…In their pioneering experiments 3 Gambardella et al demonstrated ferromagnetic order and enhanced magnetic anisotropy of monoatomic Co chains on a stepped Pt͑111͒ surface. Numerous theoretical studies followed this experiment, focusing primarily on the unusual magnetic anisotropy in this particular system.…”
Section: Introductionmentioning
confidence: 99%
“…This is a necessary (although not sufficient) condition for the emergence of intriguing magnetic properties induced by the low dimensionality, such as giant magnetic anisotropy. [28,29] Because of their high thermal stability, MOCNs similar to those presented here could thus be convenient model systems where to explore the occurrence of low-dimensional magnetism.…”
mentioning
confidence: 99%